The stock exchange and investment analysis - Briston, R. J. (London : Allen & Unwin, 1970)
The book describes the mechanism of the London Stock Exchange and the broad principles and practice of finance, investment, and investment analysis, without employing advanced mathematical techniques
Includes bibliographical references: p. 477-482.
osc 12/07/2018
Loans
Keywords: Stock exchanges; Investment analysis; Investments